Validez y fiabilidad de un dispositivo inercial (wimu protm) para el análisis del posicionamiento en balonmano - Bastida-Castillo, A.; Goez-Carmona, C. D.; Hernandez-Belmonte, A.; Pino-Ortega, J. (Revista Ciencia del Deporte, 2018)
Thanks to technological advances, new methods to analyse physiological, kinematical and spatial positioning variables have been developed. The collection of quantitative data will enable the training process enhancement in sport. Objectives: This study examined 1) the validity of the ultra-wide band (UWB) tracking technology registered by the WIMU PROTM inertial device (RealTrack Systems, Almeria, Spain) and 2) the inter-device reliability for its registering in handball. Method: Four young national-level handball players (Age: 17.43 ± 0.45 years, body mass: 78.34 ± 4.65 kg, height 1.93 ± 3.56 m) performed travels of different direction and distance: (a) court perimeter; (b) half-court line; and (c) 9-meter line. To assess the validity, the measures recorded by the device were compared with those of a track regulated by the International Handball Federation (IHF). On the other hand, the inter-device reliability was evaluated with the comparison of two inertial devices used simultaneously during the trials. The process of extract and analysis the registered data were realised by SPROTM software (RealTrack Systems, Almeria, Spain) Results: A very high validity of the assessed device was found, showing an average difference of 0.84% and 0.42% for the coordinates ''x'' and ''y'' respectively, compared to the official measurements of the court. The inter-device reliability was also very high showing values for the ''x'' coordinate (ICC=0.79) and for the ''y'' coordinate (ICC=0.68) between units. Conclusion: The WIMU PROTM device is a valid and reliable instrument for the indoor tracking analysis in handball.